ANALISIS KINERJA ORGANISASI DALAM PENYELESAIAN TINDAK LANJUT HASIL PENGAWASAN (TLHP) INSPEKTORAT PROVINSI JAWA TENGAH - Muhamad Zainul Abidin; Retna Hanani (Journal of Management and Public Policy, 2026)
Follow-up on Supervision Results (TLHP) is an important process included in the series of supervision processes where recommendations for improvement on audit findings are followed up and implemented. The completion of TLHP by the Central Java Provincial Inspectorate has not yet met the target set by the Central Java Provincial Inspectorate of 85% in several years and the process of completing the TLHP exceeds 60 days in accordance with Governor Regulation No. 14 of 2021 concerning the Handling of Follow-Up on Audit Findings in the Central Java Provincial Government. This study aims to identify and analyze the factors that contribute to organizational performance in the completion of TLHP by the Central Java Provincial Inspectorate. The study is based on the theory of organizational performance factors to identify factors that contribute to organizational performance. This study is a descriptive qualitative study. The data sources in this study were obtained through interviews and documentation. Informants were selected using purposive and snowball sampling techniques. The results of the study indicate that there are factors that contribute to encouraging and inhibiting organizational performance, which have an impact on the effectiveness of the completion of TLHP by the Central Java Provincial Inspectorate. The factors that contribute to encouragement are organizational structure, management policies, and facilities and infrastructure, while the factors that contribute to inhibition are human resources, management information systems, workload, and the complexity of recommendations.